ANALISIS PENGARUH CUSTUMER SATISFACTION DAN TRUST IN BRAND TERHADAP CUSTUMER RETENTION MELALUI SWITCHING COST SEBAGAI VARIABEL INTERVENING (Studi Kasus Pengguna Kartu TELKOMSEL Di Desa Gersik Putih Kecamatan Gapura Kabupaten Sumenep) - Asrori Tamam; N Rachma; A. Agus Priyono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT The use of telecommunications cards, especially in remote areas such as Gersik Putih Village, Gapura District, Sumenep Regency. Many things that occur dipedasaan that occur in the field of telecommunications such as network congestion caused far from the HP signal transmitter tower. The research conducted aims and analyzes whether there is an effect of customer satisfaction as X1 variable and trust in brand as X2 variable on customer retention as Y variable through switching cost as variable Z. This study used a sample of 91 people. The variables of this study consist of custumer satisfaction and trust in brand as independent variables, custumer retention as the dependent variable and switching cost as intervening variables. This study uses path analysis. The results of this study indicate that the variable custumer satisfaction has a significant level of custumer retention through switching costs and directly. While the trust in brand has a significant effect on custumer retention if through switching costs and does not have a significant effect on custumer retention directly. Switching cost itself as an intervening variable has a significant effect on custumer retention directly. Keywords : Gersik Putih Village, Costomer Satisfaction, Trust in Brand, Switching Cost, Costumer Retention.